Your Phone Has Internet - Why Are You at a Library PC? Re-imagining Public Access for the Mobile Internet Era - Donner, Jonathan (Interact: 14th IFIP TC13 Conference on Human-Computer Interaction, 2013)
This study focuses on teenage users of public internet access venues (PAVs) in low-income neighbourhoods of Cape Town. It documents their cultivation of detailed ICT repertoires to make the most of available ICTs. It highlights the continuing importance of PAVs as supplements for poorly equipped schools, and reveals the incompleteness of any supposed transition to mobile-only internet use. While the mobile internet is opening up opportunities for young people, its current form still conflicts with the easy (global) rhetoric of a closing digital divide and the end of the PAV. We recommend policy and design actions (effecting rules, training, messaging, functionality, and Wi-Fi) to reconfigure PAVs to be more useful "in the age of the mobile internet". Though some actions require support from policymakers, this is fruitful ground for designers and technologists. We identify steps which can be undertaken immediately, rather than waiting for future device convergence or lower tariffs.